2019
DOI: 10.1002/ffj.3563
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and odor characteristics of methylthiomethyl carboxylates

Abstract: Sixteen methylthiomethyl esters were prepared by the reactions of carboxylic acids with dimethyl sulfoxide and oxalyl chloride. The reactions were carried out at a low temperature by Pummerer rearrangement to produce the esters in 82‐94% yields. The odor characteristics of the esters obtained were evaluated by GC‐MS‐O and most of them possessed pleasant fruity odors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Therefore, another pathway for the formation of 4 is proposed as follows. When the reaction was carried out at higher temperature, excess DMSO attacks the methyl group of the chlorodimethylsulfonium salt 5 via a nucleophilic substitution leading to the formation of methanesulfenyl chloride ( 7 ) and a methoxydimethylsulfonium salt ( 8 ), which was reported by Bellesia et al and also observed in our related work . Just as the intermediate 5 , the intermediate methoxydimethylsulfonium salt ( 8 ) reacted with 1b as an electrophile to give an adduct, which lost CH 3 OH after a proton transfer to also generate the intermediate ( 6 ) leading to 4 as mentioned above (Scheme ).…”
Section: Results and Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, another pathway for the formation of 4 is proposed as follows. When the reaction was carried out at higher temperature, excess DMSO attacks the methyl group of the chlorodimethylsulfonium salt 5 via a nucleophilic substitution leading to the formation of methanesulfenyl chloride ( 7 ) and a methoxydimethylsulfonium salt ( 8 ), which was reported by Bellesia et al and also observed in our related work . Just as the intermediate 5 , the intermediate methoxydimethylsulfonium salt ( 8 ) reacted with 1b as an electrophile to give an adduct, which lost CH 3 OH after a proton transfer to also generate the intermediate ( 6 ) leading to 4 as mentioned above (Scheme ).…”
Section: Results and Discussionsupporting
confidence: 78%
“…A series of synthetic methods have been developed in our recent work about the application of the combination reagents of sulfoxide and oxalyl halide, including sulfenyllactonization or chlorolactonization of alkenoic acids, bromination, sulfenylchlorination, or oxysulfenylation of alkenes, dehydration of primary amides or aldoximes, sulfenyletherification of alkenols, the preparation of unsaturated lactones from 3-alkenoic acids, , and methylthiomethylation of carboxylic acids . During the investigation of oxysulfenylation of alkenes in CH 3 CN with DMSO/(COCl) 2 , an N -acetylbenzoxazine was obtained fortuitously when p -cresol was used as a nucleophile.…”
Section: Introductionmentioning
confidence: 99%